Direct observational test rules out small MgII absorbers - Pontzen, A; Hewett, P; Carswell, R; Wild, V (2007)
Recent observations suggest that the incidence of strong intervening Mg II absorption systems along the line of sight to gamma-ray burst afterglows is significantly higher than expected from analogous quasar sightlines. One possible explanation is a geometric effect, arising because Mg II absorbers only partially cover the quasar continuum regions, in which case Mg II absorbers must be considerably smaller than previous estimates. We investigate the production of abnormal absorption profiles by partial coverage and conclude that the lack of any known anomalous profiles in observed systems, whilst constraining, cannot on its own rule out patchy Mg II absorbers. In a separate test, we look for differences in the distribution function of Mg II equivalent widths over quasar continuum regions and C III emission lines. We show that these anomalies should be observable in any scenario where Mg II absorbers are very small, but they are not present in the data. We conclude that models invoking small Mg II absorbers to explain the excess of absorbers seen towards gamma-ray bursts are ruled out. © 2007 The Authors. Journal compilation © 2007 RAS.